Study on National Unity and its Results - Burenbayar, Sodbileg; Naranbold, Tumurchudur (Mongolian Journal of Strategic Studies, 2025)
National unity is a fundamental pillar of social stability and sustainable development in Mongolia, closely intertwined with citizens’ values, collective psychology, and government policy. Recent years have witnessed growing social fragmentation, ideological polarization, and mutual distrust, emphasizing the urgent need for evidence-based research to guide policies aimed at strengthening cohesion. This study is based on the 2025 “Survey on National Unity,” which investigates the principal factors that both divide and unite Mongolian society. It examines social perceptions, trust in institutions, and cultural and historical influences that shape collective identity and public attitudes. Drawing on these insights, the article proposes actionable strategies and policy recommendations to reinforce national solidarity, promote social consensus, and enhance the capacity of governance frameworks to address emerging societal challenges. Үндэсний эв нэгдлийн судалгаа, үр дүн Хураангуй: Үндэсний эв нэгдэл нь Монгол Улсын нийгмийн тогтвортой байдал, хөгжлийн үндэс бөгөөд иргэдийн үнэт зүйлийн баримжаалал, нийгмийн сэтгэл зүйн төлөв байдал, төрийн бодлоготой салшгүй холбоотой. Сүүлийн жилүүдэд нийгэмд үзэл бодлын ялгаа, хагарал, үл итгэлцэл ажиглагдаж байгаа нь үндэсний эв нэгдлийг бэхжүүлэх чиглэлээр шинжлэх ухааны үндэслэлтэй судалгаа явуулж, үр дүн дээр суурилсан бодлого боловсруулах шаардлагыг бий болгож байна. Энэ өгүүллийг 2025 онд гүйцэтгэсэн “Үндэсний эв нэгдлийн тандалт судалгаа”-ны үр дүнд тулгуурлан “Биднийг юу хагалан бутаргаж, байна вэ?”, “Биднийг юу нэгтгэж байна вэ?”, “Цаашид үндэсний эв нэгдлийг хэрхэн бэхжүүлэх вэ?” гэсэн үндсэн агуулгын хүрээнд авч үзнэ. Түлхүүр үг: Үнэт зүйл, эв нэгдэл, нийгмийн ялгарал, үндэсний ондоошил, ижилсэл